DESAIN MODEL DAN MEDIA PEMBELAJARAN BERBASIS ICT (INFORMATION AND COMMUNICATION TECHNOLOGY) PADA TINGKAT SEKOLAH DASAR - Novalina Indriyani; Darmansyah; Desyandri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2022)
This study aims to examine and analyze the importance of teachers in designing ICT-based learning models and media. Designing models and media begins with preliminary research by students. Some things that need to be understood about students are basic skills and learning styles that many students are not interested in learning. The method used in this research is descriptive-qualitative method with a literature study approach. Where researchers analyze several relevant journals and articles from previous research. Data was collected by searching for online journals through Google Scholar with the keywords learning design, learning models, learning media, ICT-based learning. The conclusions from this study indicate that the design of learning models and media must be developed in learning by teachers, such as the use of digital media in developing media, developing learning materials and developing assessments, so that each student gets meaningful and enjoyable learning.